2011
DOI: 10.1111/j.1740-8709.2010.00259.x
|View full text |Cite
|
Sign up to set email alerts
|

Excessive iodine intake during pregnancy in Somali refugees

Abstract: Iodine deficiency and excess are both associated with adverse health consequences, with fetuses, children and pregnant women being most vulnerable to the devastating effects of severe deficiency. It is often assumed that the iodine status of a population if displaced or in a remote or emergency situation is low. However, there is little evidence available to support this assumption, especially among long-term food-aid-dependent pregnant women. An effectiveness trial of a prenatal multiple-micronutrient supplem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 11 publications
0
23
0
Order By: Relevance
“…A study published in 2012 reported that the median UIC (730 μg/l) of the populations of two Somali refugee camps in Kenya who were receiving iodine supplementation were in the range consistent with excessive iodine intake. 19 In a study of >200 Chinese adults, subclinical hypothyroidism was more common in those supplemented with a 400 μg iodine tablet than in those given placebo. 20 These findings are similar to the results of other studies in Denmark 21 and New Zealand, 22 which also showed an increased prevalence of transient hyperthyroidism.…”
Section: Sources Of Iodine Excessmentioning
confidence: 99%
“…A study published in 2012 reported that the median UIC (730 μg/l) of the populations of two Somali refugee camps in Kenya who were receiving iodine supplementation were in the range consistent with excessive iodine intake. 19 In a study of >200 Chinese adults, subclinical hypothyroidism was more common in those supplemented with a 400 μg iodine tablet than in those given placebo. 20 These findings are similar to the results of other studies in Denmark 21 and New Zealand, 22 which also showed an increased prevalence of transient hyperthyroidism.…”
Section: Sources Of Iodine Excessmentioning
confidence: 99%
“…The upper limit of acceptable iodine intake in pregnancy is controversial. Iodine excess during pregnancy existed in Somalia [ 45 ], Japan and other countries. The fetal thyroid does not acquire the capacity to suppress the acute Wolff-Chaikoff effect until approximately 36 weeks of gestation [ 46 ].…”
Section: Iodine Excess During Pregnancymentioning
confidence: 99%
“…However, permanent metabolic effects of excess iodine intake could occur if the iodine source is not detected and discontinued . Excess iodine intake has been reported in China, and among African refugees in Sudan, Algeria, and Somalia, mainly associated with drinking water and the use of iodized salt …”
Section: Introductionmentioning
confidence: 99%
“…However, permanent metabolic effects of excess iodine intake could occur if the iodine source is not detected and discontinued. 19 Excess iodine intake has been reported in China, 20 and among African refugees in Sudan, 21 Algeria, 22 and Somalia, 23,24 mainly associated with drinking water and the use of iodized salt. 25,26 The Universal Salt Iodization (USI) program in Ghana mandates that all salt produced, imported, distributed, and marketed in Ghana should meet the set standards of iodine content in salt, quality, iodization, and packaging for human and animal consumption.…”
Section: Introductionmentioning
confidence: 99%